2005
DOI: 10.1111/j.1365-2958.2005.04861.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of methane oxidation in the facultative methanotroph Methylocella silvestris BL2

Abstract: SummaryThe molecular regulation of methane oxidation in the first fully authenticated facultative methanotroph Methylocella silvestris BL2 was assessed during growth on methane and acetate. Problems of poor growth of Methylocella spp. in small-scale batch culture were overcome by growth in fermentor culture. The genes encoding soluble methane monooxygenase were cloned and sequenced, which revealed that the structural genes for soluble methane monooxygenase, mmoXYBZDC , were adjacent to two genes, mmoR and mmoG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 40 publications
2
91
1
1
Order By: Relevance
“…Since pMMO is present in all known methanotrophs with the exception of Methylocella (Dedysh et al, 2000;Theisen et al, 2005) and the phylogeny of pmoA is congruent with 16S rRNA phylogeny (Kolb et al, 2003), pmoA is the most frequent target in molecular ecology studies of methanotrophs (see Dumont and Murrell, 2005 for a review). Recently, a pmoA microarray has been developed by Bodrossy and colleagues, which has proved to be particularly suitable for characterizing the diversity within methanotroph communities (Bodrossy et al, 2003(Bodrossy et al, , 2006Stralis-Pavese et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since pMMO is present in all known methanotrophs with the exception of Methylocella (Dedysh et al, 2000;Theisen et al, 2005) and the phylogeny of pmoA is congruent with 16S rRNA phylogeny (Kolb et al, 2003), pmoA is the most frequent target in molecular ecology studies of methanotrophs (see Dumont and Murrell, 2005 for a review). Recently, a pmoA microarray has been developed by Bodrossy and colleagues, which has proved to be particularly suitable for characterizing the diversity within methanotroph communities (Bodrossy et al, 2003(Bodrossy et al, , 2006Stralis-Pavese et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…are aerobic facultative methanotrophs (Alphaproteobacteria), with three validated species, M. palustris, M. silvestris and M. tundrae, isolated from acidic soils (Dunfield et al, 2003;Dedysh et al, 2000Dedysh et al, , 2004. M. silvestris BL2, which can grow on a variety of multicarbon substrates (Dedysh et al, 2005;Theisen et al, 2005), oxidizes methane using the soluble methane monooxygenase encoded by the operon mmoXYBZDC. Methylocella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Type IIa was used for the primary pmoA sequences of the Methylocystaceae . Type IIb was used to group all other Type II-related (i.e., Alphaproteobacteria ) sequences, including those from the Beijerinckiaceae (Theisen et al, 2005; Dunfield et al, 2010; Vorobev et al, 2011) and the alternate pMMO2 identified in some Methylocystis species (Dunfield et al, 2002; Baani and Liesack, 2008). …”
Section: Pmoa Taxonomymentioning
confidence: 99%